2000
DOI: 10.1007/s002140000200
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational and theoretical studies of urea and magnesium-urea complexes

Abstract: The molecular structure and IR spectra of urea, H 2 NCONH 2 , in gas phase and in acetonitrile solution, as well as of the two complexes [MgU 4 Cl 2 ] and [MgU 6 ]Cl 2 have been observed. The in¯uence of environmental changes to geometry and spectra are shown. Various basis sets have been employed to safeguard the validity of the reported ®ndings, using polarization functions for all calculations to get the correct pyramidal amide con®guration. The erroneous low energy of the C 2v symmetry group, after the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The successful intercalation was clearly shown by a significant expansion of thedggj .spacingfi-om 1.52 to 1.74 nm in the Ca-UCM (Fig. A gallery height of 0.84 nm estimated from the XRD pattern was in good agreement with the calculated diameter, approximately 0.84 nm for the Ca(urea)g^''" complex (Supplemental Table 1), strongly suggesting its presence within the interlayer space (Raptis et al, 2000). A gallery height of 0.84 nm estimated from the XRD pattern was in good agreement with the calculated diameter, approximately 0.84 nm for the Ca(urea)g^''" complex (Supplemental Table 1), strongly suggesting its presence within the interlayer space (Raptis et al, 2000).…”
Section: Intercalation Of Calcium-urea Complexsupporting
confidence: 62%
See 4 more Smart Citations
“…The successful intercalation was clearly shown by a significant expansion of thedggj .spacingfi-om 1.52 to 1.74 nm in the Ca-UCM (Fig. A gallery height of 0.84 nm estimated from the XRD pattern was in good agreement with the calculated diameter, approximately 0.84 nm for the Ca(urea)g^''" complex (Supplemental Table 1), strongly suggesting its presence within the interlayer space (Raptis et al, 2000). A gallery height of 0.84 nm estimated from the XRD pattern was in good agreement with the calculated diameter, approximately 0.84 nm for the Ca(urea)g^''" complex (Supplemental Table 1), strongly suggesting its presence within the interlayer space (Raptis et al, 2000).…”
Section: Intercalation Of Calcium-urea Complexsupporting
confidence: 62%
“…Successftil complexation could be further confirmed by the unique thermal behavior ofthe coordinated urea molecules, which showed that their stepwise release depended on the ntimber of coordinated molecules (Keuleers et al, 2000;Raptis et al, 2000). In particular, the Ca-urea complex showed a thermal response similar to that ofthe Mn-(urea)g complex (Raptis et al, 2000), which strongly indicates the formation of a Ca(urea)g^"*" complex (Supplemental Fig.…”
Section: Results and Discussion Solid-state Synthesis Of Metal-urea Cmentioning
confidence: 78%
See 3 more Smart Citations